Diabetes in the elderly. (November 2022) - Abdelhafiz, Ahmed H.; Sinclair, Alan J.
Abstract: The prevalence of diabetes mellitus is increasing, and its epidemiology is shifting towards old age because of increased life expectancies. As a result, diabetes mellitus is increasingly becoming a disease of older rather than middle age. The increased prevalence of co-morbidities associated with ageing, combined with the increased prevalence of geriatric syndromes that lead to physical and mental disabilities and frailty, contributes to the complexity of managing diabetes in elderly individuals. Taking into account the heterogeneous functional status, co-morbidities, frailty and life expectancy of older people, therapeutic interventions and glycaemic targets should be individualized, considering individuals' preferences and putting quality of life at the heart of their care plans.